Design and Performance Analysis of 6LoWPAN Wireless Sensor Networks for Smart Buildings Management - Esmail Mahmoud Ali Esmail; Taha E. Alhoudire; Adel Ali Alsonousi Saeid; Osama Mohammed Hassan Elhodairi; Mohamed Abdurrhman Salem Alhodiri (Journal of Scientific and Human Dimensions, 2025)
This study presents a comprehensive performance analysis of 6LoWPAN-based Wireless Sensor Networks for smart building management systems. A MATLAB simulation framework was developed to model a three-story building environment with 60 sensor nodes and one border router. The simulation incorporated realistic indoor propagation models accounting for wall attenuation (10 dB) and floor attenuation (20 dB). Results demonstrate robust network performance with a Packet Delivery Ratio (PDR) of 92.4%, average end-to-end latency of 87.3 ms, and network connectivity of 96.7%. The average hop count was 2.8 with a maximum of 5 hops, while energy efficiency remained at 100% throughout the 2-hour simulation period. These findings confirm 6LoWPAN’s suitability for real-time building automation applications, meeting the reliability and responsiveness requirements for HVAC control, lighting management, and environmental monitoring in modern smart buildings.